Serum levels of Vitamin A and Atopic Rhinoconjunctivitis in Swedish adolescents - Malin Barman; Nils-Gunnar Carlsson; Anna Sandin; Agnes E. Wold; Ann-Sofi e Sandberg (Journal of Food Science and Nutrition Therapy - Peertechz Publications, 2017)
Aim: Vitamin A plays a role in mucosal immunity and tolerance, but the association between vitamin A status and allergy is still unclear. The aim of the study was to analyze the levels of vitamin A in serum from adolescents with or without atopic rhinoconjunctivitis. Method: Thirteen-year-old children with atopic rhinoconjunctivitis (n = 53) and non-allergic, nonsensitized controls (n = 52) were randomly selected from a population based prospective birth cohort comprising 1228 children in Northern Sweden born in 1996-1997. Vitamin A (retinol) concentrations in serum were measured with high performance liquid chromatography mass spectrometry. Multiple logistic regression was used to evaluate the association between allergy prevalence and serum vitamin A levels. Results: Multiple logistic regression analysis showed no association between serum vitamin A levels and atopic rhinoconjunctivitis prevalence; OR = 1.00 (95% confidence interval 1.00-1.00), p = 0.81.       Stratification for gender revealed a trend for a higher risk for having atopic rhinoconjunctivitis with higher concentrations of vitamin A in serum for females, OR = 1.02 (1.00-1.05), p = 0.07. No such associations were found in male subjects OR = 0.99 (0.97-1.01), p = 0.15. A dose-response relationship between allergy and vitamin A concentrations were also calculated but no such relationships were found, neither for all subjects nor for male and females separately. Conclusions: Serum levels of vitamin A could neither be positively nor negatively associated with atopic rhinoconjunctivitis in Swedish teenagers.